Binder and preparation method thereof, positive electrode sheet and preparation method thereof, and aqueous halogen battery
Patent Information
- Application Number
- CN202610871857.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-16
- Publication Date
- 2026-10-23
AI Technical Summary
[0003]然而,水系卤素电池的商业化进程仍面临严峻挑战
(1)协同抑制穿梭效应,提升循环稳定性。本申请通过阳离子聚合物的静电锚定与官能团化碳纳米管的三维限域形成协同机制,强力吸附卤素离子并物理阻挡多卤化物扩散,有效抑制穿梭效应,从而在高质量负载下仍能保持高库伦效率和优异的循环稳定性。
Smart Images

Figure CN122958978A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of battery technology, specifically relating to a binder and its preparation method, a positive electrode sheet and its preparation method, and an aqueous halogen battery. Background Technology
[0002] In recent years, with the rapid growth of portable electronic devices, electric vehicles, and the grid connection of renewable energy, the global demand for advanced and reliable energy storage systems has become increasingly urgent. In the process of transitioning to a sustainable energy ecosystem, developing efficient and environmentally friendly energy storage solutions has become a focus of industry attention. Lithium-ion batteries, as the mainstream energy storage technology for a long time, have shown inherent limitations during large-scale deployment, particularly in terms of safety risks, environmental impact, and dependence on scarce and geopolitically sensitive raw materials, prompting the active exploration of alternative battery technologies. Against this backdrop, aqueous halogen batteries, with their advantages of high theoretical capacity, excellent rate performance, abundant raw material sources, low cost, and intrinsic safety, have become a highly promising alternative.
[0003] However, the commercialization of aqueous halogen batteries still faces significant challenges. The shuttle effect prevalent in halogen cathodes leads to severe loss of active material, causing irreversible self-discharge and reducing coulombic efficiency. Simultaneously, the low conductivity and slow reaction kinetics of halogen species limit the battery's power performance. Furthermore, the high proportion of inactive materials in existing electrode systems makes it difficult for the overall energy density of the battery to meet practical application requirements. To address these issues, existing technologies often employ strategies such as cathode material control, anode surface modification, and separator structure design. However, these methods often bring new problems, including complex manufacturing processes, significantly increased costs, and further reductions in the proportion of active material.
[0004] In battery systems, binders are a crucial component of electrodes. Compared to other battery components, binders typically account for only 2%-5% of the total battery mass, and their cost represents less than 1% of the total battery manufacturing cost. However, as an indispensable functional component in electrode slurry preparation, the structure and properties of binders have a decisive impact on the interfacial stability of the electrode, the construction of the conductive network, and the utilization rate of active materials.
[0005] Therefore, there is an urgent need to provide a novel binder that can effectively suppress the shuttle effect of halogen cathodes, increase the loading of active materials to improve energy density, and improve electron and ion transport efficiency, so as to promote the practical development of aqueous halogen batteries. Summary of the Invention
[0006] To address the aforementioned technical problems, this application provides a binder and its preparation method, a positive electrode sheet and its preparation method, and an aqueous halogen battery. The binder uses polysaccharide-structured polymers, functionalized carbon nanotubes, and cationic polymers as raw materials. Through esterification between the polysaccharide-structured polymer and the functionalized carbon nanotubes, hydrogen bond self-assembly is enhanced, constructing a three-dimensional interpenetrating network with excellent conductivity and elasticity. The functionalized carbon nanotubes construct a three-dimensional conductive framework to reduce internal resistance and buffer deformation, while the cationic polymer inhibits polyhalide shuttle through electrostatic anchoring. Through this synergistic mechanism, the binder can reduce the proportion of inactive materials, improve energy density and structural stability, while enabling the positive electrode to maintain excellent electrochemical performance under high-mass loading. Furthermore, the raw materials are green and inexpensive, and the process is simple, making it suitable for large-scale application in aqueous halogen batteries.
[0007] To achieve the above objectives, this application adopts the following technical solution: In a first aspect, the present invention provides an adhesive, the raw materials for which include: a polysaccharide-structured polymer, a cationic polymer, and functionalized carbon nanotubes; The polysaccharide structure polymer includes at least one of carboxyl-containing polysaccharide structure polymers and carboxyl-free polysaccharide structure polymers. The cationic polymer includes at least one of polyethyleneimine, cationic polyacrylamide, polyquaternary ammonium salt, and polylysine; The functionalized carbon nanotubes include at least one of carboxylated carbon nanotubes, hydroxylated carbon nanotubes, and aminolated carbon nanotubes.
[0008] Optionally, the mass ratio of the polysaccharide-structured polymer to the cationic polymer is 1:(0.1-3); and / or The mass ratio of the polysaccharide-structured polymer to the functionalized carbon nanotubes is 1:(0.1-3).
[0009] Optionally, the carboxyl-containing polysaccharide structural polymer includes at least one of carboxymethyl cellulose, carboxyethyl cellulose, sodium alginate, xanthan gum, and gum arabic; and / or The carboxyl-free polysaccharide structural polymer includes at least one of starch, chitosan, guar gum, and carrageenan; and / or The polyquaternary ammonium salt includes at least one of polyquaternary ammonium salt-5, polyquaternary ammonium salt-7, polyquaternary ammonium salt-10, and polydiallyldimethylammonium chloride.
[0010] Secondly, this application provides a method for preparing an adhesive as described in any one of the first aspects above, comprising the following steps: The polysaccharide polymer and the cationic polymer were added to deionized water and stirred to obtain a transparent solution. The functionalized carbon nanotubes and the catalyst were added to the transparent solution and ultrasonically treated to obtain a black solution; wherein, the polysaccharide structure polymer containing carboxyl groups reacted with carboxylated carbon nanotubes, hydroxylated carbon nanotubes and / or aminated carbon nanotubes, and the polysaccharide structure polymer without carboxyl groups reacted with carboxylated carbon nanotubes. The black solution was freeze-dried to obtain the adhesive.
[0011] Optionally, the catalyst comprises at least one of 4-dimethylaminopyridine, 4-piperidinylpyridine, and 4-(1-pyrrolidinyl)pyridine.
[0012] Optionally, in the transparent solution, the total mass fraction of the polysaccharide-structured polymer and the cationic polymer is 1%-20%; and / or The catalyst accounts for 0.05%-0.4% of the total mass of the binder.
[0013] Thirdly, this application provides a positive electrode sheet comprising the binder as described in any one of the first aspects above.
[0014] Fourthly, this application provides a method for preparing a positive electrode sheet as described in the third aspect above, comprising the following steps: Mix 0.5-2.5 parts by weight of activated carbon, 0.05-0.3 parts by weight of binder, and 1-10 parts by weight of deionized water to prepare a mixed slurry; The mixed slurry is coated onto the current collector and dried to obtain a dried activated carbon electrode sheet; The positive electrode active material is loaded onto the activated carbon dry electrode sheet and dried to obtain the positive electrode sheet.
[0015] Optionally, the activated carbon includes at least one of coal-based activated carbon, wood-based activated carbon, and fruit shell activated carbon; and / or The current collector includes at least one of stainless steel mesh, titanium foil, titanium mesh, graphite paper, and carbon fiber cloth; and / or The positive electrode active material includes iodine, bromine, sulfur; and / or The areal density of the activated carbon dried electrode sheet is 10 mg·cm³. -2 -30 mg·cm -2 ; and / or The positive electrode active material loading per unit area of the positive electrode sheet is 10 mg·cm³. -2 -30 mg·cm -2 .
[0016] In addition, this application also provides an aqueous halogen battery, including the positive electrode as described in the third aspect above.
[0017] Compared with the prior art, this application has the following advantages: (1) Synergistic suppression of shuttle effect and improvement of cycling stability. This application forms a synergistic mechanism by electrostatic anchoring of cationic polymer and three-dimensional confinement of functionalized carbon nanotubes, which strongly adsorbs halogen ions and physically blocks the diffusion of polyhalides, effectively suppressing the shuttle effect, thereby maintaining high coulombic efficiency and excellent cycling stability under high mass loading.
[0018] (2) Constructing a three-dimensional conductive network that balances high energy density and fast kinetics. Functionalized carbon nanotubes construct a continuous three-dimensional interpenetrating network in a flexible matrix, which significantly reduces internal resistance and accelerates reaction kinetics through stable point-to-surface contact; at the same time, it replaces some traditional conductive agents, reduces the proportion of inactive materials, and simultaneously improves electrode conductivity and overall energy density.
[0019] (3) Enhance mechanical flexibility and structural stability. The three-dimensional network formed by hydrogen bond self-assembly through esterification has both excellent conductivity and elasticity. It can improve its mechanical strength through physical entanglement and chemical bonding, and effectively buffer the volume deformation during charging and discharging, prevent the active particles from being pulverized and falling off, and maintain the integrity of the electrode structure and interface stability.
[0020] (4) The raw materials are green and inexpensive, and the process is suitable for large-scale production. The use of polysaccharides, natural polymers and common carbon materials is environmentally friendly and inexpensive; the preparation method is simple and convenient, without the need for complex equipment, which helps to reduce the manufacturing cost of aqueous halogen batteries and promotes large-scale industrial application. Attached Figure Description
[0021] To more clearly illustrate the embodiments of the present invention, the accompanying drawings involved in the embodiments will be briefly described below. For those skilled in the art, other related drawings can be obtained from the above drawings without any creative effort.
[0022] Figure 1 Fourier transform infrared spectrum of the adhesive prepared in Example 1; Figure 2 Images of films prepared using the adhesive prepared in Example 1 and a commercially available adhesive, respectively; Figure 3 This is a comparison chart of the long-cycle performance of zinc-iodine full cells assembled with the positive electrode sheets prepared in Example 5 and Comparative Example 1. Figure 4 This is a comparison chart of the rate performance of zinc-iodine full cells assembled with the positive electrode sheets prepared in Example 5 and Comparative Example 1. Figure 5 This is a comparison of the cyclic voltammetry curves of zinc-iodine full cells assembled with the positive electrode sheets prepared in Example 5 and Comparative Example 1. Figure 6This is a comparison of the self-discharge performance of zinc-iodine full cells assembled with the positive electrode sheets prepared in Example 5 and Comparative Example 1. Figure 7 The electrochemical impedance spectroscopy comparison diagrams are shown for zinc-iodine full cells assembled from the positive electrode sheets prepared in Example 5 and Comparative Example 1. Detailed Implementation
[0023] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. It should be particularly noted that the following embodiments are only for illustrating this application and do not limit the scope of this application. Similarly, the following embodiments are only some embodiments of this application, not all embodiments. All other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0024] Unless otherwise specified, the experimental methods involved in the embodiments of this application are all conventional methods; the materials, reagents, instruments, equipment, etc. used are all commercially available unless otherwise specified.
[0025] In this document, the term "implementation" means that a specific feature, structure, or characteristic described in connection with an implementation may be included in at least one implementation of this application. The appearance of this phrase in various places in the specification does not necessarily refer to the same implementation, nor is it a separate or alternative implementation mutually exclusive with other implementations. It will be explicitly and implicitly understood by those skilled in the art that the implementations described herein can be combined with other implementations.
[0026] This application provides an adhesive, the raw materials of which include: a polysaccharide-structured polymer, a cationic polymer, and functionalized carbon nanotubes; The polysaccharide structure polymer includes at least one of carboxyl-containing polysaccharide structure polymers and carboxyl-free polysaccharide structure polymers. The cationic polymer includes at least one of polyethyleneimine, cationic polyacrylamide, polyquaternary ammonium salt, and polylysine; The functionalized carbon nanotubes include at least one of carboxylated carbon nanotubes, hydroxylated carbon nanotubes, and aminolated carbon nanotubes.
[0027] In this embodiment, the functionalized carbon nanotubes (such as carboxylated, hydroxylated, or aminated carbon nanotubes) are not only conductive fillers but also key reinforcing phases for constructing three-dimensional functional networks. They improve hydrophilicity and dispersion stability in aqueous slurries through surface polar functional groups and form a through-type three-dimensional conductive framework within a flexible matrix. This stable point-to-surface contact significantly reduces ohmic resistance and charge transfer impedance, accelerating electron transport in halogen conversion reactions. Simultaneously, the functionalized carbon nanotubes undergo esterification with polysaccharide polymers to form covalent crosslinks. The conductive network is firmly anchored in the binder skeleton by strong hydrogen bonds and association with cationic polymers to effectively prevent slippage or breakage of the conductive network during electrode drying, rolling, and long-cycle processes. In addition, the nanofiber reinforcement effect of one-dimensional high-modulus carbon nanotubes is utilized to improve the tensile strength and toughness of the binder through load transfer and physical entanglement. This allows the rigid-flexible coupled network to effectively absorb volumetric strain during charging and discharging, inhibiting active particle pulverization and coating cracking, and ultimately realizing the transformation from an "inert conductive additive" to a "conductive-reinforcing-anchoring multifunctional component".
[0028] In specific embodiments, when the polysaccharide structure polymer is a carboxyl-containing polysaccharide structure polymer (containing both carboxyl and hydroxyl groups), the functionalized carbon nanotubes include at least one of carboxylated carbon nanotubes, hydroxylated carbon nanotubes, and aminated carbon nanotubes; when the polysaccharide structure polymer is a carboxyl-free polysaccharide structure polymer (containing only hydroxyl groups), the functionalized carbon nanotubes include carboxylated carbon nanotubes; when the polysaccharide structure polymer is a carboxyl-containing polysaccharide structure polymer and a carboxyl-free polysaccharide structure polymer, the functionalized carbon nanotubes include at least one of carboxylated carbon nanotubes, hydroxylated carbon nanotubes, and aminated carbon nanotubes.
[0029] In some embodiments, the carboxyl-containing polysaccharide structural polymer includes at least one of carboxymethyl cellulose, carboxyethyl cellulose, sodium alginate, xanthan gum, and gum arabic.
[0030] In some embodiments, the carboxyl-free polysaccharide structural polymer includes at least one of starch, chitosan, guar gum, and carrageenan.
[0031] In this embodiment, the polysaccharide-structured polymer is not only an interfacial binder but also a core framework for constructing a three-dimensional conductive and elastic network. Its mechanism of action is as follows: First, multi-scale interfacial bonding is achieved based on physical interactions. Polysaccharide-structured polymers form hydrogen bond networks and physical entanglements with active materials and carbon nanotubes through hydroxyl groups and polar functional groups (such as carboxyl and amino groups), providing excellent cohesive force and interfacial adhesion to ensure the integrity of the electrode structure.
[0032] Secondly, covalent / coordination crosslinking enhancement is achieved based on chemical reactivity. Utilizing the chemical reactivity of polysaccharide polymers, carboxyl-containing polysaccharide polymers (e.g., carboxymethyl cellulose, carboxyethyl cellulose, sodium alginate, xanthan gum, gum arabic) react with carboxylated, hydroxylated, and / or aminated carbon nanotubes, while carboxyl-free polysaccharide polymers (e.g., starch, chitosan, guar gum, carrageenan) react with carboxylated carbon nanotubes. This "esterification-enhanced hydrogen bond self-assembly" mechanism firmly anchors carbon nanotubes within the polymer matrix, constructing a three-dimensional interpenetrating network with both high conductivity and high elasticity, preventing slippage and breakage of the conductive network.
[0033] Furthermore, the polysaccharide segments of the polysaccharide-structured polymer also possess ion transport and synergistic confinement functions. Their moderate hydrophilicity constructs nanoscale hydrated ion channels to promote halide ion transport, while the negatively charged polysaccharide chains form polyelectrolyte complexes with cationic polymers, synergistically inhibiting polyhalide shuttle through electrostatic shielding effects, thereby achieving a transformation from "passive bonding" to "active construction of functional networks".
[0034] In some embodiments, the mass ratio of the polysaccharide-structured polymer to the cationic polymer is 1:(0.1-1).
[0035] In some embodiments, the mass ratio of the polysaccharide-structured polymer to the cationic polymer can be 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:2.0, 1:2.2, 1:2.4, 1:2.6, 1:2.8, 1:3.0, or within the range defined by any two of the above values.
[0036] In some embodiments, the mass ratio of the polysaccharide-structured polymer to the functionalized carbon nanotubes is 1:(0.1-3).
[0037] In some embodiments, the mass ratio of the polysaccharide-structured polymer to the functionalized carbon nanotubes can be 1:0.1, 1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6, 1:0.7, 1:0.8, 1:0.9, 1:1, 1:1.1, 1:1.2, 1:1.3, 1:1.4, 1:1.5, 1:1.6, 1:1.7, 1:1.8, 1:2.0, 1:2.2, 1:2.4, 1:2.6, 1:2.8, 1:3.0, or within the range defined by any two of the above values.
[0038] In the embodiments of this application, the cationic polymer can form a dense ionic cross-linked network with the polysaccharide structure polymer through hydrogen bonding and electrostatic complexation, which not only improves the cohesive strength of the binder but also endows it with excellent flexibility, thereby effectively buffering the volume deformation during charging and discharging. At the same time, the positively charged groups on the cationic polymer molecular chain form a strong anchoring effect on halogen ions through electrostatic adsorption, which significantly inhibits polyhalide shuttle and greatly improves the cycle stability of the battery.
[0039] In some implementations, the polyquaternium salt includes at least one of polyquaternium salt-5, polyquaternium salt-7, polyquaternium salt-10, and polydiallyldimethylammonium chloride.
[0040] This application further provides a method for preparing an adhesive as described in any of the above claims, comprising the following steps: The polysaccharide polymer and the cationic polymer were added to deionized water and stirred to obtain a transparent solution. The functionalized carbon nanotubes and the catalyst were added to the transparent solution and ultrasonically treated to obtain a black solution; wherein, the polysaccharide structure polymer containing carboxyl groups reacted with carboxylated carbon nanotubes, hydroxylated carbon nanotubes and / or aminated carbon nanotubes, and the polysaccharide structure polymer without carboxyl groups reacted with carboxylated carbon nanotubes. The black solution was freeze-dried to obtain the adhesive.
[0041] In some embodiments, the catalyst comprises at least one of 4-dimethylaminopyridine, 4-piperidinylpyridine, and 4-(1-pyrrolyl)pyridine.
[0042] In some embodiments, the total mass fraction of the polysaccharide-structured polymer and the cationic polymer in the transparent solution is 1%-20%.
[0043] In some embodiments, the total mass fraction of the polysaccharide polymer and the cationic polymer in the transparent solution may be 1%, 5%, 10%, 15%, 20%, or within the range defined by any two of the above values.
[0044] In some embodiments, the catalyst accounts for 0.05%-0.4% of the total mass of the binder, for example, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.4%, or within the range defined by any two of the above values.
[0045] This application further provides a positive electrode sheet, including the binder as described in any of the preceding embodiments.
[0046] This application further provides a method for preparing a positive electrode sheet as described above, comprising the following steps: Mix 0.5-2.5 parts by weight of activated carbon, 0.05-0.3 parts by weight of binder, and 1-10 parts by weight of deionized water to prepare a mixed slurry; The mixed slurry is coated onto the current collector and dried to obtain a dried activated carbon electrode sheet; The positive electrode active material is loaded onto the activated carbon dry electrode sheet and dried to obtain the positive electrode sheet.
[0047] In some embodiments, the activated carbon may be 0.5 parts, 0.8 parts, 1.0 parts, 1.2 parts, 1.5 parts, 1.8 parts, 2.0 parts, or 2.5 parts by weight, or within the range defined by any two of the above values.
[0048] In some embodiments, the adhesive may be 0.05, 0.08, 0.1, 0.12, 0.15, 0.18, 0.2, 0.25, or 0.3 parts by weight, or within the range defined by any two of the above values.
[0049] In some embodiments, the deionized water may be 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts, or 10 parts by weight, or within the range defined by any two of the above values.
[0050] In some embodiments, the activated carbon includes at least one of coal-based activated carbon, wood-based activated carbon, and fruit shell activated carbon.
[0051] In some embodiments, the current collector includes at least one of stainless steel mesh, titanium foil, titanium mesh, graphite paper, and carbon fiber cloth.
[0052] In some embodiments, after the mixed slurry is coated onto the current collector, the drying temperature is 50-100°C.
[0053] In some embodiments, the loading method for loading the positive electrode active material onto the activated carbon dry electrode sheet includes at least one of the following: drip impregnation, electroplating, and thermal sublimation.
[0054] In some embodiments, after loading the positive electrode active material onto the activated carbon dry electrode sheet, the drying temperature is 20-60°C.
[0055] In some embodiments, the positive electrode active material includes iodine, bromine, and sulfur.
[0056] In some embodiments, the areal density of the activated carbon dried electrode sheet is 10 mg·cm³. -2 -30 mg·cm-2 For example, it can be 10 mg·cm -2 13mg·cm -2 16mg·cm -2 19mg·cm -2 21mg·cm -2 24mg·cm -2 27mg·cm -2 30mg·cm -2 Or, within the range defined by any two of the above values.
[0057] In some embodiments, the positive electrode active material loading per unit area of the positive electrode sheet is 10 mg / cm². -2 -30 mg·cm -2 For example, it can be 10 mg·cm -2 13mg·cm -2 16mg·cm -2 19mg·cm -2 21mg·cm -2 24mg·cm -2 27mg·cm -2 30mg·cm -2 Or, within the range defined by any two of the above values.
[0058] In addition, this application also provides an aqueous halogen battery, including the positive electrode sheet as described in the above embodiments.
[0059] It should be noted that, based on the same positive electrode structure and manufacturing process, those skilled in the art can adapt the positive electrode sheet of this application to various aqueous metal-halogen battery systems, such as aqueous zinc-iodine batteries, aqueous zinc-bromine batteries, aqueous lithium-iodine batteries, aqueous sodium-iodine batteries, aqueous calcium-iodine batteries, aqueous potassium-iodine batteries, or aqueous aluminum-iodine batteries, by selecting different halogen elements (such as fluorine, chlorine, bromine, and iodine) and matching the corresponding negative electrode materials. All of these fall within the scope of protection claimed in this application.
[0060] To further illustrate the technical effects of the present invention, the following specific embodiments are also provided.
[0061] Example 1 Example 1 provides an adhesive and its preparation method, comprising the following steps: At room temperature, 0.5 parts by mass of a polysaccharide-structured polymer (carboxymethyl cellulose) and 1.0 parts by mass of a cationic polymer (polyethyleneimine) were weighed and added to 6.0 parts by mass of deionized water. The mixture was stirred and mixed to obtain a transparent solution. 1.0 parts by mass of functionalized carbon nanotubes (carboxylated carbon nanotubes) and 0.004 parts by mass of a catalyst (4-dimethylaminopyridine) were added to the obtained transparent solution. The mixture was ultrasonically dispersed for 30 min and then freeze-dried to obtain a black solid binder.
[0062] Example 2 Example 2 provides an adhesive, the preparation method of which is basically the same as that of Example 1, the only difference being the raw materials and formulation as follows: 1 part by mass of a polysaccharide-structured polymer (carboxyethyl cellulose), 0.2 parts by mass of a cationic polymer (polyethyleneimine), 1.2 parts by mass of a functionalized carbon nanotube (hydroxylated carbon nanotube), and 0.003 parts by mass of a catalyst (4-(1-pyrrolidinyl)pyridine).
[0063] Example 3 Example 3 provides an adhesive, the preparation method of which is basically the same as that of Example 1, the only difference being the raw materials and formulation as follows: 1 part by mass of a polysaccharide-structured polymer (sodium alginate), 0.3 parts by mass of a cationic polymer (polylysine), 0.5 parts by mass of a functionalized carbon nanotube (aminated carbon nanotube), and 0.002 parts by mass of a catalyst (4-dimethylaminopyridine).
[0064] Example 4 Example 4 provides an adhesive, the preparation method of which is basically the same as that of Example 1, except that the raw materials and formulation are as follows: 1 part by mass of a polysaccharide-structured polymer (carrageenan), 1 part by mass of a cationic polymer (cationic polyacrylamide), 1 part by mass of a functionalized carbon nanotube (carboxylated carbon nanotube), and 0.005 parts by mass of a catalyst (4-(1-pyrrolidinyl)pyridine).
[0065] Example 5 Example 5 provides an iodine positive electrode sheet and its preparation method, comprising the following steps: 1.0 parts by weight of activated carbon, 0.1 parts by weight of black solid binder, and 4.0 parts by weight of deionized water were added to a beaker and stirred at 500 rpm for 4 h at 25 °C to obtain a mixed slurry. The mixed slurry was uniformly coated on the surface of a current collector (titanium mesh) and then dried at 60 °C for 6 h to obtain a dried activated carbon electrode sheet (the areal density of the dried activated carbon electrode sheet is 14 mg·cm³). -2An anhydrous ethanol solution of iodine was added dropwise to the activated carbon dried electrode sheet prepared above, and dried at 40 °C for 1 h to obtain an iodine positive electrode sheet. The surface loading of the active material (iodine) on this positive electrode sheet was determined to be 12 mg·cm³. -2 .
[0066] Comparative Example 1 Comparative Example 1 provides an iodine positive electrode control sample and its preparation method, comprising the following steps: 1.0 parts by weight of activated carbon, 0.1 parts by weight of carboxymethyl cellulose, and 4.0 parts by weight of deionized water were added to a beaker and stirred at 500 rpm for 4 h at 25 °C to obtain a mixed slurry. The mixed slurry was uniformly coated onto the surface of a current collector (titanium mesh) and then dried at 60 °C for 6 h to obtain a dried activated carbon electrode (the areal density of the dried activated carbon electrode is 14 mg·cm³). -2 An anhydrous ethanol solution of iodine was added dropwise to the activated carbon dried electrode sheet prepared above, and dried at 40 °C for 1 h to obtain an iodine positive electrode sheet control sample. The surface loading of the active material (iodine) on this positive electrode sheet control sample was determined to be 12 mg·cm³. -2 .
[0067] Test Example 1 The adhesive prepared in Example 1 of this application was subjected to Fourier transform infrared spectroscopy (FT-IR) to characterize its internal chemical bonding mode.
[0068] like Figure 1 As shown, curve a is the FT-IR spectrum of the cationic polymer, curve b is the spectrum of the polysaccharide structure polymer (sodium carboxymethyl cellulose), curve c is the spectrum of the physical mixture of the cationic polymer and the polysaccharide structure polymer, and curve d is the spectrum of the adhesive prepared in Example 1.
[0069] Compared to single-component adhesives, the binder (curve d) showed better performance at 3300 cm⁻¹. -1 The nearby broad peaks broadened significantly and redshifted. These peaks are attributed to the stretching vibrations of -OH and -NH. The broadening and shift of the peak shape indicate that a dense, strong hydrogen-bonded association network and ion-dipole interactions have formed between the polysaccharide polymer, the cationic polymer, and the functionalized carbon nanotubes. At the same time, some of the -OH groups involved in the esterification reaction were consumed, leading to a decrease in the peak intensity in this region. Together, these factors confirm the existence of strong interfacial bonding between the components.
[0070] More importantly, at 1776 cm -1 A new characteristic peak belonging to the stretching vibration of the ester carbonyl group (ν(C=O)) appeared at 1251 cm⁻¹, while at 1251 cm⁻¹... -1 The ν-coc asymmetric stretching vibration (ν) belonging to the ester bond COC was observed at this location. asThe novel characteristic peaks (COC) were observed. These two characteristic peaks were not present in the original single component, directly confirming that the -COOH on the surface of the carboxylated carbon nanotubes underwent an esterification crosslinking reaction with the -OH of the polysaccharide polymer, successfully constructing a stable covalent crosslinking network. These results indicate that the binder provided in Example 1, in addition to physical mixing, also exhibits strong hydrogen bonding and covalent crosslinking formed by esterification, validating the concept of multiple synergistic effects proposed in this application.
[0071] Test Example 2 Test Example 2 compared the film-forming properties and mechanical flexibility of a commercial adhesive with the adhesive prepared in Example 1 of this application, including the following steps: 0.2 parts by weight of commercial adhesive (carboxymethyl cellulose, CMC) and 0.2 parts by weight of the adhesive prepared in Example 1 were weighed and added to 100 parts by weight of deionized water respectively. The mixtures were stirred at 25°C for 6 h to form a homogeneous solution. The two solutions were then poured into polytetrafluoroethylene molds and dried at 60°C for 12 h. The film samples were then demolded to obtain the film samples.
[0072] like Figure 2 As shown, the film prepared from commercial carboxymethyl cellulose is hard and brittle, and is extremely easy to break; while the film prepared from the binder of Example 1 of this application has excellent flexibility and good bending resilience, indicating that the binder of Example 1 of this application effectively overcomes the brittleness problem of traditional single polysaccharide binders through the construction of multiple networks.
[0073] Test Example 3 Test Example 3 provides an assembly method and electrochemical performance test for a zinc-iodine full cell, including the following steps: (1) Battery assembly The battery was assembled using a button cell structure, with the following stacking order: negative electrode shell, spring sheet, gasket, zinc sheet negative electrode, glass fiber separator, positive electrode sheet, and positive electrode shell. The electrolyte was a 2 mol / L zinc sulfate aqueous solution. The experimental group used the iodine positive electrode sheet prepared in Example 5, while the control group used the iodine positive electrode sheet prepared in Comparative Example 1 (using a single carboxymethyl cellulose binder).
[0074] (2) Electrochemical performance testing At room temperature, the assembled zinc-iodine full cell was subjected to constant current charge-discharge test using the Xinwei Battery Testing System.
[0075] Long-cycle performance testing: The voltage window was set at 0.6 V-1.6 V, and the current density was 1 A·g. -1 .like Figure 3 As shown, the experimental group of batteries using the binder of Example 5 of this application cycled stably for more than 5,500 cycles under these conditions, demonstrating excellent cycle stability.
[0076] Rate performance test: The voltage window was set to 0.6 V-1.6 V, and the current density was set to 0.1 A·g. -1 0.2 A·g -1 0.3 A·g -1 1 A·g -1 2 A·g -1 3 A·g -1 and at 0.1 A·g -1 Next, perform a recovery test. Figure 4 As shown, the rate performance and capacity recovery rate of the experimental group batteries were significantly better than those of the control group, indicating that the binder in this application effectively improved the kinetic performance and structural stability of the electrodes.
[0077] Test Example 4 Test Example 4 involves performing a cyclic voltammetry (CV) test on the zinc-iodine full cell assembled in Test Example 3, including the following steps: The experimental group battery (positive electrode of Example 5) assembled in Test Example 3 and the control group battery (positive electrode of Comparative Example 1) were tested at a scan rate of 0.1 mV·s. -1 The voltage window was set to 0.6 V-1.6 V. The test results are as follows: Figure 5 As shown, compared with the control group, the experimental group battery has a larger CV curve integral area and a smaller redox peak potential difference, indicating that it has higher electrochemical reactivity and better redox reversibility.
[0078] Test Example 5 Test Example 5 tests the self-discharge performance of the zinc-iodine full cell assembled in Test Example 3, including the following steps: The test subjects were the experimental group battery (positive electrode of Example 5) and the control group battery (positive electrode of Comparative Example 1) assembled in Test Example 3. The test procedure was as follows: First, at 1 A·g -1 The electrode was activated by cycling 10 times at a current density within a voltage range of 0.6 V to 1.6 V; then the battery was charged to 1.6 V and left to stand in the open circuit at room temperature for 72 h.
[0079] Test results are as follows Figure 6 As shown, the voltage decay rate of the experimental group battery (positive electrode of Example 5) was significantly lower than that of the control group (positive electrode of Comparative Example 1). This is due to the multiple adsorption sites formed by the cationic polymer and functionalized carbon nanotubes in the binder, which can effectively suppress the polyiodide shuttle effect generated during charging and discharging, thereby endowing the battery with excellent anti-self-discharge capability.
[0080] Test Example 6 Test Example 6 involves electrochemical impedance spectroscopy testing of the zinc-iodine full cell assembled in Test Example 3, including the following steps: The test subjects were the experimental group battery (positive electrode of Example 5) assembled in Test Example 3 and the control group battery (positive electrode of Comparative Example 1). Before the test, the batteries were first subjected to 1 A·g -1 The battery was cycled 50 times at a current density of 0.6 V to 1.6 V. Subsequently, electrochemical impedance spectroscopy was performed on the cycled battery using a Shanghai Chenhua electrochemical workstation, with a frequency range of 0.01 Hz to 100 kHz and an amplitude of 0.05 mV.
[0081] Test results are as follows Figure 7 As shown, the charge transfer resistance of the experimental group battery (positive electrode of Example 5) was significantly lower than that of the control group (positive electrode of Comparative Example 1). This indicates that the three-dimensional conductive network and strong interfacial interaction constructed by the binder in this application effectively reduce the ion transport barrier at the electrode / electrolyte interface, improve reaction kinetics, and thus endow the battery with better rate performance and cycle stability.
[0082] In summary, this application provides a binder and its preparation method, a positive electrode and its preparation method, and an aqueous halogen battery. The binder uses polysaccharide-structured polymers, functionalized carbon nanotubes, and cationic polymers as raw materials. Through esterification between the polysaccharide-structured polymer and the functionalized carbon nanotubes, hydrogen bond self-assembly is enhanced, constructing a three-dimensional interpenetrating network with excellent conductivity and elasticity. The functionalized carbon nanotubes construct a three-dimensional conductive framework to reduce internal resistance and buffer deformation, while the cationic polymer inhibits polyhalide shuttle through electrostatic anchoring. Through this synergistic mechanism, the binder can reduce the proportion of inactive materials, improve energy density and structural stability, while maintaining excellent electrochemical performance of the positive electrode under high-mass loading. Furthermore, the raw materials are green and inexpensive, and the process is simple, making it suitable for large-scale application in aqueous halogen batteries.
[0083] It is understood that the technical features of the above embodiments can be combined arbitrarily. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0084] The specific embodiments of the present invention have been described above. It should be understood that the scope of protection of the present invention is not limited thereto. Those skilled in the art should understand that any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention fall within the scope of protection and disclosure of the present invention.
Claims
1. An adhesive, characterized in that, The raw materials for preparation include: polysaccharide-structured polymers, cationic polymers, and functionalized carbon nanotubes; The polysaccharide structure polymer includes at least one of carboxyl-containing polysaccharide structure polymers and carboxyl-free polysaccharide structure polymers. The cationic polymer includes at least one of polyethyleneimine, cationic polyacrylamide, polyquaternary ammonium salt, and polylysine; The functionalized carbon nanotubes include at least one of carboxylated carbon nanotubes, hydroxylated carbon nanotubes, and aminolated carbon nanotubes.
2. The adhesive according to claim 1, characterized in that, The mass ratio of the polysaccharide-structured polymer to the cationic polymer is 1:(0.1-3); and / or The mass ratio of the polysaccharide-structured polymer to the functionalized carbon nanotubes is 1:(0.1-3).
3. The adhesive according to claim 1, characterized in that, The carboxyl-containing polysaccharide structural polymer includes at least one of carboxymethyl cellulose, carboxyethyl cellulose, sodium alginate, xanthan gum, and gum arabic; and / or The carboxyl-free polysaccharide structural polymer includes at least one of starch, chitosan, guar gum, and carrageenan; and / or The polyquaternary ammonium salt includes at least one of polyquaternary ammonium salt-5, polyquaternary ammonium salt-7, polyquaternary ammonium salt-10, and polydiallyldimethylammonium chloride.
4. A method for preparing an adhesive as described in any one of claims 1-3, characterized in that, Includes the following steps: The polysaccharide polymer and the cationic polymer were added to deionized water and stirred to obtain a transparent solution. The functionalized carbon nanotubes and the catalyst were added to the transparent solution and ultrasonically treated to obtain a black solution; wherein, the polysaccharide structure polymer containing carboxyl groups reacted with carboxylated carbon nanotubes, hydroxylated carbon nanotubes and / or aminated carbon nanotubes, and the polysaccharide structure polymer without carboxyl groups reacted with carboxylated carbon nanotubes. The black solution was freeze-dried to obtain the adhesive.
5. The method for preparing the adhesive according to claim 4, characterized in that, The catalyst includes at least one of 4-dimethylaminopyridine, 4-piperidinylpyridine, and 4-(1-pyrrolidinyl)pyridine.
6. The method for preparing the adhesive according to claim 4, characterized in that, In the transparent solution, the total mass fraction of the polysaccharide-structured polymer and the cationic polymer is 1%-20%; and / or The catalyst accounts for 0.05%-0.4% of the total mass of the binder.
7. A positive electrode sheet, characterized in that, Includes the adhesive as described in any one of claims 1-3.
8. A method for preparing a positive electrode sheet as described in claim 7, characterized in that, Includes the following steps: Mix 0.5-2.5 parts by weight of activated carbon, 0.05-0.3 parts by weight of binder, and 1-10 parts by weight of deionized water to prepare a mixed slurry; The mixed slurry is coated onto the current collector and dried to obtain a dried activated carbon electrode sheet; The positive electrode active material is loaded onto the activated carbon dry electrode and dried to obtain the positive electrode.
9. The method for preparing the positive electrode sheet according to claim 8, characterized in that, The activated carbon includes at least one of coal-based activated carbon, wood-based activated carbon, and fruit shell activated carbon; and / or The current collector includes at least one of stainless steel mesh, titanium foil, titanium mesh, graphite paper, and carbon fiber cloth; and / or The positive electrode active material includes iodine, bromine, sulfur; and / or The areal density of the activated carbon dried electrode sheet is 10 mg·cm³. -2 -30 mg·cm -2 ; and / or The positive electrode active material loading per unit area of the positive electrode sheet is 10 mg·cm³. -2 -30 mg·cm -2 .
10. An aqueous halogen battery, characterized in that, Includes the positive electrode sheet as described in claim 7.